The Influence of Product Design, Features, and Quality Specifications on Interest in Buying an iPhone Mini - Octaviani, Anandayu; Rahmawan, Ginanjar (prodima@fe.uika-bogor.ac.id, 2023)
The purpose of this research is to determine the effect of product design, features, and quality specifications on the intention to buy the iPhone Mini and to see the effect of product design, features, and quality specifications simultaneously on the intention to buy the iPhone Mini. The method used is the quantitative method. The test implements data instrument testing, classic assumption testing, and hypothesis testing. Sampling implements non probability sampling technique with purposive sampling. The results of the sample acquisition consisted of 170 iPhone user respondents in all regions of Indonesia via Google from which had been distributed. The results of the study show that product design, feature, and specification quality variables partially and simultaneously have a significant effect on the intention to buy the iPhone Mini.